Evaluation of pre- and post-pyriform plasty nasal airflow - Sofia,Oscimar Benedito (2018)
Abstract Introduction: Nasal obstruction is a frequent complaint in otorhinolaryngology outpatient clinics, and nasal valve incompetence is the cause in most cases. Scientific publications describing surgical techniques on the upper and lower lateral cartilages to improve the nasal valve are also quite frequent. Relatively few authors currently describe surgical procedures in the piriform aperture for nasal valve augmentation. We describe the surgical technique called pyriform plasty and evaluate its effectiveness subjectively through the NOSE questionnaire and objectively through the rhinomanometry evaluation. Objective: To compare pre- and post-pyriform plasty nasal airflow variations using rhinomanometry and the NOSE questionnaire. Methods: Eight patients submitted to pyriform surgery were studied. These patients were screened in the otorhinolaryngology outpatient clinic among those who complained of nasal obstruction, and who had a positive response to Cottle maneuver. They answered the NOSE questionnaire and were submitted to preoperative rhinomanometry. After 90 days, they were reassessed through the NOSE questionnaire and the postoperative rhinomanometry. The results of these two parameters were compared pre- and postoperatively. Results: Regarding the subjective measure, the NOSE questionnaire, seven patients reported improvement, of which two reported marked improvement, and one patient reported an unchanged obstructive condition. Regarding the rhinomanometry assessment, of 96 comparative measurements between the preoperative and postoperative periods, we obtained 68 measurements with an increase in nasal airflow in the postoperative period, 26 negative results, and two cases that remained unaltered between the preoperative and postoperative periods. Conclusion: When analyzing the results obtained in this study, we can conclude that the piriform plasty surgical procedure resulted in nasal airflow improvement in most of the obtained measurements.